PEMBUATAN ES KRIM LIDAH BUAYA (ALOE CHINENSIS) DENGAN PENAMBAHAN GELLING AGENTS - Elfi Anis Saati, Titik Sundari (Jurnal Bestari, 2009)
The utilization of Aloe vera as healthy food can be consumed in the form of ice cream. Moreover, the objective of this article is to find the interaction of gelling agents' type and level of concentration in the process of making Aloe vera ice cream. The study was conducted using random design of factorial group with two factors. First factor was the type of gelling agents consisted of three levels (CMC, Arabian Gum, Na-alginat). Meanwhile, second factor was gelling agents concentration consisted of three levels (0,1%; 0,3%; 0,5%) (b/v). Thus, the result was nine combinations with three times repetition.